(untitled) (Al-Aasar, 2025)
This Article, titled “A Study of Makoosi Lughat, A Reverse Dictionary of Urdu” is a study of the valuable work of Dr. Donald A.Becker. Dr. Donald A.Becker published this reversed order Dictionary by the cooperation of American Philosophical Society (Pen Rose Fund). This dictionary consists of 261 pages. It was published by Ramesh Jain Manohar Publication, Ansari Road Darya Ganj New Dehli in 1980. This article critically examines technical issues regarding writing reverse order dictionary and highlights the technical mistakes of this reverse order dictionary.